Opening Spaces for Indigenous Teaching and Learning through Community-Based Teacher Education - Shelley Tulloch; Sylvia Moore (University of Aberdeen, School of Education, 2018)
Following Nunatsiavut land claims on the Northeast Atlantic coast in Canada, Memorial University and the Nunatsiavut Government partnered to offer a community-based, Inuit-specific Bachelor of Education (IBED). This program was developed to lay a foundation for Inuit-governed schools. In the context of a broader research project on the development and mobilization of Inuit educational leaders in northern Canada, we listened to the stories of Inuit pre-service teachers, instructors, and administrators who contributed to the first IBED program. Analysis of their narratives shows how the physical location of the program opened learning spaces for Inuit students who were unwilling or unable to study outside their home region. We also discuss how program developers and instructors interpreted "community-based" to include anchoring learning in community relationships with each other and with local knowledge holders, as well as learning in and from the natural environment. Inuit and non-Inuit instructors modelled the incorporation of Inuit language, knowledges, culture, and pedagogies across the curriculum. We suggest that these processes opened ideological spaces which enhanced student engagement and retention and prepared the pre-service teachers to be agents of change in Inuit schools